SENIOR HIGH SCHOOL STUDENTS’ CONFIDENCE IN SPEAKING ENGLISH - Lia Angelina; Melvina Melvina; Yelfiza Yelfiza (Universitas PGRI Sumatera Barat, 2025)
This study intended to find out the level of students’ confidence in speaking English at SMA N 9 Bungo viewed from four aspects: believing in their ability, taking decisions independently, having positive feelings toward themselves, and being brave to express their opinions. The type of the study was quantitative with a survey research design. The study focused on gathering data from 64 students. In collecting the data, the questionnaire was used to obtain students’ self-confidence, consisting of 34 statements. The data collected were analyzed quantitatively using descriptive statistics in frequency, mean, and standard deviation using the Statistical Package for Social Science program (SPSS). The result of the study showed that students’ self-confidence was categorized into low levels based on the four aspects of Self-confidence. Based on this condition, English teachers must find out possible strategies to solve students’ lack of self-confidence in speaking to help them competent to use the language in communication.